1984
DOI: 10.1152/jappl.1984.56.2.315
|View full text |Cite
|
Sign up to set email alerts
|

Availability of glucose given orally during exercise

Abstract: Adequate utilization of glucose given orally during prolonged muscular exercise remains a matter of controversy. The aim of the present study was to investigate whether the time when glucose is ingested during exercise affects exogenous glucose disposal. Nine healthy male volunteers were submitted to a 4-h period of treadmill exercise at about 45% of their maximum O2 consumption. A 100-g load of naturally labeled [13C]glucose was given orally after 120 min (5 subj, group A) or 15 min (4 subj, group B) of exerc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
11
0
2

Year Published

1985
1985
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(13 citation statements)
references
References 0 publications
0
11
0
2
Order By: Relevance
“…7 It was only after the late 1970's and early 1980's that 13c and 14c labelling techniques were used to calculate rates of ingested CHO oxidation during exercise (Lefebvre et al 1975;Lefebvre et al 1979;Pirnay et al 1977aPirnay et al , 1977bPirnay et al , 1982Jandrain et al 1984Jandrain et al , 1989Krzentowski et al 1984;Massicotte et al 1986Massicotte et al , 1989Massicotte et al , 1990Pallikarakis et al 1986;Peronnet et al 1990;Hawley et al 1992a;Moodley et al 1992). Such studies were, on the whole performed on cyclists, possibly because it is easier to take blood from a cyclist on a stationary ergometer that from a runner on a treadmill.…”
Section: Introduction and Historical Overviewmentioning
confidence: 99%
See 1 more Smart Citation
“…7 It was only after the late 1970's and early 1980's that 13c and 14c labelling techniques were used to calculate rates of ingested CHO oxidation during exercise (Lefebvre et al 1975;Lefebvre et al 1979;Pirnay et al 1977aPirnay et al , 1977bPirnay et al , 1982Jandrain et al 1984Jandrain et al , 1989Krzentowski et al 1984;Massicotte et al 1986Massicotte et al , 1989Massicotte et al , 1990Pallikarakis et al 1986;Peronnet et al 1990;Hawley et al 1992a;Moodley et al 1992). Such studies were, on the whole performed on cyclists, possibly because it is easier to take blood from a cyclist on a stationary ergometer that from a runner on a treadmill.…”
Section: Introduction and Historical Overviewmentioning
confidence: 99%
“…In some cases, the oxidation of ingested CHO has been reported to contribute only 5 -10% of total CHO oxidation (Costill et al 1973;Van Handel et al 1980) but those studies are the exception. The majority of trials have shown that the contribution from ingested glucose to total CHO oxidation during exercise is between 18 to 40% (Pirnay et al 1977a;Jandrain et al 1984Jandrain et al , 1989Decombaz et al 1985;Massicotte et al 1986Massicotte et al , 1989Massicotte et al , 1990Hawley et al 1992b) and up to 68% in fasted subjects (Pallikarakis et al 1986). …”
mentioning
confidence: 99%
“…De façon surprenante, alors que l'on sait ou que l'on soupçonne que la sélection des substrats et l'oxydation des glucides exogènes à l'exercice pourraient être modifiées chez des sujets dont la tolérance au glucose est compromise, peu d'études ont été conduites chez le su-jet obèse (Ravussin et al, 1980) et chez le sujet diabétique (Krzentowski et al, 1981;Riddell et al, 2000a;Robitaille et al, 2007). Il existe également peu de données systématiques sur l'effet du mode d'administration des glucides exogènes [bolus vs doses (Massicotte et al, 1996a) ; ingestion avant vs pendant l'exercice Caron et al, 2004;Krzentowski et al, 1984a) ; effet de la concentration de la solution ingérée (Jandrain et al, 1989;Jentjens et al, 2004bJentjens et al, , 2006Moodley et al, 1992)] sur leur oxydation. Un certain nombre d'études se sont penchées, par contre, sur l'effet de l'entraînement Jeukendrup et al, 1997;Krzentowski et al, 1984b;Péronnet et al, 2009;van Loon et al, 1999), de l'état nutritionnel (Ravussin et al, 1979), de certains facteurs environnementaux [froid (Galloway et al, 2001), chaud (Jentjens et al, 2006(Jentjens et al, , 2002, hypoxie (Péronnet et al, 2006)] et de certains nutriments ou agents pharmacologiques dont on sait qu'ils interfèrent ou pourraient interférer avec la digestion et l'absorption des glucides et la sélection des substrats [acarbose qui inhibe les glucosidases (Gerard et al, 1986), sodium (Massicotte et al, 1996b) qui pourrait faciliter l'absorption du glucose par le « sodium-glucose transporter 1 » (SLGT1) , métoclopramide qui accélère la vidange gastrique (Massicotte et al, 1996b), acipimox qui bloque la lipolyse (Gautier et al, 1994) ; caféine (Desbrow et al, 2009;Hulston et Jeukendrup, 2008;Yeo et al, 2005)].…”
Section: Vue D'ensemble Des éTudesunclassified
“…Plusieurs évidences suggèrent qu'au cours de l'effort prolongé à une puissance de travail faible, sans ingestion de glucides, les sujets utilisent une grande proportion de lipides (∼60-85 %En) , 1977Romijn et al, 1993 et très peu de glycogène musculaire (Romijn et al, 1993. Dans cette troisième étude de la thèse, à partir des observations effectuées à des puissances de travail similaires , 1977Krzentowski et al, 1984a;Péronnet et al, 2009;, nous avons émis l'hypothèse qu'une fraction importante du 6 glucose ingéré serait oxydée et que les glucides, et non les lipides, seraient les principaux substrats oxydés. …”
unclassified
“…As a result, hypoglycemia may ensue both during intensive, short-term exercise (11) or moderate long-term physical work (12). If carbohydrate solutions are taken during exercise, insulin secretion is stimulated less than in the resting state (13). Thus, carbohydrate solutions taken during long-term exercise are effective in maintaining plasma glucose concentrations and improving endurance performance (14).…”
mentioning
confidence: 99%